Molecular prevalence of Anaplasma marginale, Babesia bigemina, and Theileria orientalis and their associations with Mafriwal cattle’s age groups - Ab Manap, Muhamad Ali Hanapiah; Ahmad Mustaza, Nur Sabrina; Nasruddin, Nur Amalina; Wan Abdullah, Wan Ladiana; Yaakub, Halimatun; Hayyan, Basripuzi Nurul (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study was designed to determine the molecular prevalence of hemoparasites and their associations with Mafriwal cattle’s age groups. Materials and Methods: Blood samples were taken from the coccygeal veins of calves (n = 92), yearlings (n = 95), lactating (n = 90), and dry (n = 94) cows, which were subjected to microscopic and molecular identification of hemoparasites. The prevalence rate was determined based on the proportion of infected samples in the observed samples. Associations between hemoparasitism and different age groups of Mafriwal cattle were determined by the odds ratio and Fisher’s exact test. Results: Babesia bigemina was the most prevalent hemoparasite in monospecies infection (20.8%), while the co-infection of Anaplasma marginale and B. bigemina (36.4%) had the highest molecular prevalence. Highly significant associations of hemoparasitism were observed between calves and yearlings (p < 0.001, Odds ratio = 21.340, 95% CI = 3.200–907.871), lactating (p < 0.01, Odds ratio = 6.600, 95% CI = 1.808–36.516), and dry (p < 0.001, Odds ratio = 10.457, 95% CI = 2.363–96.242) cows. Nevertheless, calves and yearlings were 2–4 times more likely to be co-infected with multiple hemoparasite species in comparison to older age groups. Conclusion: Mafriwal cattle were more susceptible to hemoparasitism with advancing age, but the younger calves were more prone to be co-infected with multiple hemoparasite species. Adv. Vet. Anim. Res., 11(2): 384-391, June 2024 http://doi.org/10.5455/javar.2024.k787